The Effect of Business Literation on SMEs Performance with Mediation of Risk Management and Entrepreneurial Self Efficacy - Bambang Widarno (Journal of Digital Marketing and Halal Industry, 2021)
Literacy is the main prerequisite for intellectual growth and the ability to learn to generate new knowledge. This study aims to analyze the effect of business literacy on the performance of SMEs, either directly or indirectly by including the Entrepreneurial Self-Efficacy (ESE) and Enterprise Risk Management (ERM) variables as mediation and moderation variables, respectively. The approach of this article is thought or conceptual based on intellectualization and reflects the prospects and impact of digital marketing. This study uses a critical system to analytically review digital marketing literature and relate it to research results. The data analysis technique used is descriptive. Based on the results of tracking and analysis, there has never been any previous research that examines business literacy, ESE, ERM, and SME performance in one model. The implication of social justice in the field of business literacy is through the existence of a business application system that is socialized to business people. Business information can enhance or even suppress the effects of entrepreneurial self-efficacy. ERM as a planned action is a control activity, which can be perceived not as an obstacle to gaining profits, but to get the expected performance results.